Prevalence and Incidence of Insulin Dependent Diabetes Mellitus (IDDM) in Fars province in the South of Iran, 2016-17: An Insurance Archived-Prescription-based Study - Sanaz Amiri; Forough Saki; Mozhgan Seif; Alireza Mirahmadizadeh (Shiraz University of Medical Sciences, 2021)
Background: Insulin-dependent diabetes mellitus (IDDM) or type 1 diabetes mellitus (T1DM) is known as a chronic autoimmune disease with an increasing prevalence and incidence. This study was conducted to determine the incidence rate and prevalence of insulin-dependent diabetes in Iran in 2016 and 2017.   Methods: In this cross-sectional study, the prevalence of IDDM in insured subjects under the age of 19 was measured through the prescribed insulin in two consecutive years. In this study, we assumed that IDDM patients are those who receive at least one prescription containing any insulin over 2 years in insurance databases. This study was   carried out on 98% of patients under age 19, and the prevalence and incidence of IDDM were calculated. Finally, the result of this method was compared with Integrated Health System (IHS) databases. Results: In general, 1,135,105 insured persons under 19 years of age were enrolled in this study, and the prevalence rates of IDDM in subjects under 19 were 117.6 (111.5-124.2) and 136.8 (130.1-143.8) per 100,000 in 2016 and 2017, respectively. The incidence rate of this disease was 27.4 (24.6-30.8) per 100,000. The highest incidence and prevalence were significantly observed in the age group of 14-19 years. The prevalence of IDDM was not significantly different between boys and girls. Conclusion: The results of this study showed that the method of prescription follow up was appropriate, acceptable, convenient, and accurate. Our findings showed that the incidence and prevalence of IDDM in this method were in line with other worldwide reliable and accurate reports, even in the developed countries. The results of the present study showed that the prevalence and incidence rate of IDDM in Iran (Fars province) is at an intermediate level.